Pancreas Histology of Hyperglycemia of Mice (Mus musculus L.) After Treatment Basil (Ocimum x africanum Lour.) Leaf Extract and Papaya (Carica papaya L.) - Elsa Safitri; Sutyarso Sutyarso; Sri Wahyuningsih; Rochmah Agustrina (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2023)
Hyperglycemia is a condition in which the level of glucose in the blood is abnormally high. Hyperglycemia is caused by disturbances in the metabolic system in secreting insulin. Hyperglycemia if left unchecked can cause a disease which is usually called diabetes. Basil (Ocimum x africanum Lour.) and papaya (Carica papaya L.) leaf extracts can reduce blood glucose levels in people with diabetes mellitus because they contain active compounds of flavonoids, alkaloids and tannins which function as anti-diabetics. The aim of this study was to examine the effectiveness of the effects of basil and papaya leaf in affecting the level of islet damage, and repairing pancreatic histological damage in hyperglycemic mice. This study used a completely randomized design with 5 treatment groups and 5 replications. Group K(N) as normal control, group K(+) as positive control, group K (-) as negative control, group P 1 (alloxan induced and treated with ethanol extract of basil leaves 24.5 mg/35g BW mice) 14 days oral) , P 2 group (induced by alloxan and treated with papaya leaf ethanol extract 24.5 mg/35 g BW mice (14 days oral). Data on the level of histological damage to the pancreas of hyperglycemic mice were analyzed using the Kruskal-Wallis method and the Wilcoxon-MannWhitney test at a significant level of 5%. Data histological appearance of the Langerhans were analyzed descriptively.The results showed basil leaf extract and papaya had an effect on the level of damage to the pancreas of mice, basil leaf extract was effective compared to papaya in histological repair of the mice pancreas.